Development of beverage from cornsilk treated with different thermal treatments and its effect on morphological characterization, mineral composition, physicochemical properties, and sensory qualities - Shuhaiminudin, Nur Syafarah (Universiti Sains Malaysia, 2016)
Cornsilk is the by-product of maize and traditionally has being used to treat many ailments since ancient time. Utilization of cornsilk into beverage product not only able to prevent huge wastage, but also can offer alternative remedy to the consumers. This study aims to investigate the effect of different thermal treatments of cornsilk on morphological characterization, mineral compositions, physicochemical properties, and sensory properties. Cornsilk was introduced into two types of thermal treatments (steaming and blanching), and untreated. After the treatments, the comsilk was dried overnight in an oven before viewed using scanning electron microscope (SEM) for morphological characterization. Later, the dried comsilk was ground into powder form prior to beverage preparation. Both powder and beverage prepared from different treatments were analysed for mineral concentration determination using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). There was no significant differences between fresh and dried cornsilk treated with different thermal treatments in morphological features and physical characteristics. Differences were only observed in the diameter and width in all cornsilk samples. Shrinkage was obviously seen in dried comsilk samples compared to fresh comsilk samples. The result of ICP-MS showed significant amount of K and Ca compared to other macroininerals in both powder and cornsilk beverages. Similarly, the concentration of Mn and Zn were significant in both powder and comsilk beverages. For heavy metals, cornsilk powder contain low amount of Cr whereas cornsilk beverage contain low amount of Ar but still under the limit set by Food Act 1983 and Food Regulations 1985. Steamed cornsilk beverage recorded highest total soluble solids value (TSS) and pH value while untreated cornsilk beverage (UCB) recorded highest titratable acidity value (TA). Similarly for sensory evaluation, no significant differences observed from the results whereby the scoring of attributes for all cornsilk beverages samples was likely similar from each other. However, the degree of acceptance from the sensory evaluation was ranked as follows; UCB > SCB > BCB. Reformulation of the cornsilk beverages is suggested to improve acceptancy.